The Acari Hypothesis, VI: human sebum and the cutaneous microbiome in allergy and in lipid homeostasis - Retzinger, Andrew C.; Retzinger, Gregory S. (Frontiers in Allergy, 2024)
The Acari Hypothesis posits that acarians, i.e., mites and ticks, are causative agents of IgE-mediated conditions. This report further develops The Hypothesis, providing rationale for the childhood predilection of allergy. In short, Malassezia, a fungus native to human skin and utterly dependent on sebaceous lipids, prevents allergy by deterring acarians. Because sebum output is limited before puberty, children are more prone to allergy than are adults. Competition for sebaceous lipids by Staphylococcus aureus influences not only Malassezia number—and, consequently, allergic predisposition—but also lipid homeostasis. The latter, in turn, contributes to dyslipidemia and associated conditions, e.g., the metabolic syndrome.